High energetic electron distribution tails for nonlinear collisional kinetic equation in the presence of heating - Potapenko, I.F.; Soboleva, T.K.; Krasheninnikov, S.I. (Вопросы атомной науки и техники, 2008)
The time-depended solutions of collisional electron kinetic equation with the heating term allowing the solutions in self-similar variables are considered. A broader class of the heating terms resulting in enhancement of the tail of the distribution function in comparison with Maxwellian is analyzed both analytically and numerically. The results obtained can be used for the assessment of the impact of superthermal electrons on heat transport for divertor plasma as well as for the benchmarking of sophisticated kinetic codes. Рассматриваются зависящие от времени решения столкновительного электронного кинетического уравнения с нагревом, которые допускают представление в автомодельных переменных. Анализируется аналитически и численно широкий класс операторов нагрева, который приводит к росту хвоста функции распределения по сравнению с максвелловским. Полученные результаты могут быть использованы для оценки влияния сверхтепловых электронов на перенос тепла для диверторной плазмы, а также в качестве теста для сложных кинетических кодов. Розглядаються залежні від часу рішення зіштовхувального електронного кінетичного рівняння з нагріванням, що допускають представлення в автомодельних змінних. Аналізується аналітично і чисельно широкий клас операторів нагрівання, що приводить до росту хвоста функції розподілу в порівнянні з максвеллівським. Отримані результати можуть бути використані для оцінки впливу надтеплових електронів на перенос тепла для диверторної плазми, а також як тест для складних кінетичних кодів.